Gain scheduling PID control with pitch moment rejection for reducing vehicle dive and squat - Ahmad, Fauzi (Inderscience Enterprises, 2009)
This paper presents a derivation of a full vehicle model to study vehicle dynamics behaviour in longitudinal direction. The full vehicle model is then validated using an instrumented experimental vehicle based on the driver input from brake and throttle pedals. Two tests are performed for the purpose of model validation, namely, sudden braking and sudden acceleration test. The results of the validation show that the behaviours of the model closely follow the behaviour of a real vehicle. An active suspension control system is then developed on the validated full vehicle model to reduce unwanted vehicle motions during braking and throttling manoeuvres. The proposed controller structure for the active suspension system is gain scheduling PID control with pitch moment rejection loop. The results show that the proposed control structure is able to significantly improve the dynamic performance of the vehicle during sudden braking and sudden acceleration under various conditions.